THE IMPACT OF WEARING FACE MASKS ON HEALTH: A CASE OF AFGHANISTAN (The Research of Medical Science Review, 2024)
This study investigates the health impacts of wearing face masks within the context of Afghanistan, a country with unique socio-cultural, economic, and healthcare challenges. The COVID-19 pandemic has highlighted the importance of face masks in reducing the spread of infectious diseases globally, but the adoption and effects of prolonged mask use in Afghanistan warrant specific attention. This paper explores the effectiveness of face masks in controlling disease transmission, as well as the potential physical and psychological effects of extended mask use in Afghan populations. Key concerns include skin irritation, respiratory discomfort, and accessibility issues, especially in rural and under-resourced areas. The findings aim to provide culturally relevant insights to guide health policies and public health messaging in Afghanistan, ensuring that recommendations on mask use are both effective and adaptable to local conditions. This study also discusses the balance between the protective health benefits and the practical challenges of mask-wearing, aiming to support informed decision-making in the Afghan healthcare system.